PENYULUHAN TENTANG KEWENANGAN PEMERINTAH DALAM PENGEMBANGAN PENDIDIKAN BERDASARKAN UNDANG- UNDANG NO. 20 TAHUN 2003 DI YAYASAN PERKASA KARUNIA LUHUR TANGERANG - Rahim, Abdur; Almadani, Husna Aulia; Ramadhan, Dieni; Jannah, Indah Ismaul; Sakinah, Nabila; Wulansari, Tri Utami; Ulhaq, Dhiya; Haq, Dipa Dinul (Jurnal Abdimas Bina Bangsa, 2024)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self- control, personality, intelligence, noble morals, and the skills needed by themselves, society, nation and state. The national education system is all educational components that are interconnected in an integrated manner to achieve national education goals. This Community Service activity aims to provide legal counseling assistance related to educational development to the community, especially the Tangerang community. The title of this activity is "Information on Government Authority in Education Development Based on Law no. 20 of 2003 at the Perkasa Karunia Luhur Foundation, Tangerang”. Law no. 20 of 2003 concerning the National Education System which provides the legal basis for regulating government authority in developing education in Indonesia. In general, the Law stipulates that the government has a central role in establishing policies, standards and strategies in developing a national education system that is equitable, just and high quality. Education is one of the important services that must be mandated by the government. From Community Service (PKM) activities carried out on March 21 2024 with the title Counseling on Government Authority in Education Development Based on Law No. 20 of 2003 at the Perkasa Karunia Luhur Foundation, Tangerang. In Law No. 20 of 2003 there are 3 education systems, namely, formal education, non-formal education and informal education. That what the Perkasa Karunia Luhur Tangerang Foundation does is included in non-formal education, because this foundation has provided non-formal education for some people who need educational services. The non-formal education that is already running at this foundation is the Religious Education Place (TPA) which is held Monday to Saturday. The aim of holding TPA is to increase knowledge about the basics of religion and moral education for students